Penerapan Teknologi Reverse Osmosis Berdaya Panel Surya Untuk Pemurnian Air Sumur dalam Rangka Penyediaan Air Bersih di SDN Inpres Arso X: Proyek Percontohan - Asmuruf, Frans Augusthinus; Assa, Inriyanti; Mandik, Yohanis Irenius; Poli, Ivonne; Kareth, Zakaria Victor (JURNAL PENGABDIAN PAPUA, 2025)
The Community Service (PkM) activity has been carried out with the PkM partner, SD Negeri Inpres Arso X, in Keerom District, Papua, Indonesia. The issue faced by the PkM partner is its dependence on well water as the primary source of water for daily activities. However, the well water does not meet hygiene standards and is contaminated by bacteria, chemicals, or other pollutants that pose health risks, especially for children. Additionally, the limited access to electricity in Arso X creates a need for alternative power to operate the water purification system. This PkM activity aims to address these issues by implementing a solar-powered Reverse Osmosis system to purify the well water owned by the PkM partner. The PkM activities consist of three stages. First is the preparation stage, where the PkM team surveyed the location and interviewed the PkM partner. The next step involved designing the solar panel mounts, the RO system, and supporting electrical components. During the implementation stage, the PkM team conducted awareness sessions via short interactive lecture on the importance of clean water and the role of renewable energy, followed by a demonstration of water purification using solar-powered RO technology. The monitoring and evaluation phase showed that the PkM partner has benefited from the application of the solar-powered RO technology. Furthermore, regular maintenance of the RO system and solar panels is necessary.